National central banks and the governance of the European System of Central Banks - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2024)
The paper analyses the role of national central banks (NCBs) in the governance of the European System of Central Banks (ESCB), NCBs are the owners of the European Central Bank (ECB), and their governors dominate the ECB's Governing Council, but in monetary policy operations, NCBs are subordinated to the ECB, The dominance of NCB governors has materially affected Governing Council decisions on relations between NCBs and the ECB, allowing the NCBs to maintain some of their erstwhile glory, sometimes in contradiction to the primary law. Examples involve the monetary funding of investments declared as non-monetary, violations of Treaty provisions for the allocation of income from monetary policy operations, and accounting rules that obfuscate the boundary between ECB-subordinate and independent activities of NCBs, The net effect of these developments is to enlarge the domain of NCB activities.
hdl:21.11116/0000-000E-70E9-D
Keywords: E50; E58; F53; 330; European Monetary Union; European System of Central Banks; Governance of the Eurosystem; ANFA; ELA; PSPP; Central-Bank Accounting and Balance Sheets